The prevalence of underweight in children aged 5 years and younger attending primary health care clinics in the Mangaung area, Free State - Danae Koetaan; Andrea Smith; Anke Liebenberg; Marietjie Brits; Christos Halkas; Maresa Van Lill; Gina Joubert (AOSIS, 2018)
Background: The Constitution of South Africa stipulates that all children have the right to basic nutrition; however, a great number of South African children are underweight for age. It is important to address malnutrition as it is associated with more than 50% of all child deaths in developing countries and also increases the risk for infective diseases. Aim: To determine the prevalence of underweight in children aged 5 years and younger attending primary health care clinics in the Mangaung area, Free State, and determine the possible underlying causes thereof. Setting: Six preselected primary health care clinics in the Mangaung area. Methods: This was a cross-sectional study. Demographic and clinical information and anthropometric measurements were collected from the children's Road-to-Health clinic cards,obtained from the children's caregivers. Results: In total, 240 children were included, of which 51.7% were girls. The median age was 7.5 months. The weight-for-age graph revealed that 7.7% (95% confidence interval: 4.8%;11.9%) of children were underweight or severely underweight for age. Length-for-age and weight-for-height graphs were mostly incomplete. Underweight children differed from normal weight children regarding birth weight (low birth weight 70.6% vs. 12.4%) and history of malnutrition (60.0% vs. 7.1%). Conclusion: The prevalence of underweight in children aged 0-5 years attending primary health care clinics in Mangaung is 7.7% based on information available from Road-to-Health cards. This figure could be higher if these cards were filled in more accurately. A low birth weight and history of malnutrition are associated with underweight.